1982
DOI: 10.1021/es00100a009
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of brominated alkylphenol polyethoxy carboxylates in mutagenic waste water concentrates

Abstract: Removal and formation of mutagenic activity during advanced wastewater treatment were investigated by using the Salmonella typhimurium strain TA100. The activity of direct acting mutagens appeared to increase at the recarbonation stage, where 6-10 mg/L of chlorine was added. Subsequent activated carbon treatment removed activity effectively but was apparently ineffective in removing precursors. Final chlorination typically with 25 mg/L of chlorine led to the reoccurrence of mutagenicity. Organic concentrates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 17 publications
3
86
0
Order By: Relevance
“…The concentrations of NTA and NDA were significantly lower than the EDTA concentration, presumably in part due to biological removal during secondary treatment [7]. As in previous studies, partially oxidized residues of alkylphenoxy ethoxylates (APEs) were detected [2]. However, the APE residues detected here were carboxylated on both side chains, the ethoxy and the alkyl …”
Section: Quantitationsupporting
confidence: 57%
See 1 more Smart Citation
“…The concentrations of NTA and NDA were significantly lower than the EDTA concentration, presumably in part due to biological removal during secondary treatment [7]. As in previous studies, partially oxidized residues of alkylphenoxy ethoxylates (APEs) were detected [2]. However, the APE residues detected here were carboxylated on both side chains, the ethoxy and the alkyl …”
Section: Quantitationsupporting
confidence: 57%
“…A previous study of WF21 effluents (1979)(1980)(1981)(1982) found that none of the EPA priority pollutants were present at concentrations above Correspondence to: W.-H. Ding regulatory levels [1]. Other studies at WF21 focused on alkylphenol polyethoxylates surfactant residues, their chlorination and bromination during chlorine disinfection [2], and on removal of organics during reverse osmosis treatment [3]. Little is known about the identity and concentration of specific organics that remain after GAC contacting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the studies on the concentration of APE biodegradation intermediates chlorinated OPE were found in river water sampies (Sheldon and Hites [13]), while chlorination of wastewaters resulted in the formation of both chlorinated and brominated OPE and OPEC (Ball and Reinhard [108], Reinhard et al [109]) with halogenated OP2EC the major product. A wide range of halogenated OPE were determined in the municipal secondary sewage treatment plant effiuent at concentrations up to 51 J.lg/I while nonhalogenated OPE residues were present at concentrations of 36-112 J.lg/I.…”
Section: Sewage Treatmentmentioning
confidence: 99%
“…Three AP-4-tert-butylphenol (4-tBP), 4-nonylphenol (4-NP), and 4-tert-octylphenol (4-tOP)-and BPA have frequently been found in waste water, natural water, and sewage effluents [1][2][3][4]. These compounds have been closely studied in recent years because they have been shown to have estrogenic effects in fish, avian, and mammalian cells and are suspected of having endocrine-disrupting toxicity [5,6].…”
Section: Introductionmentioning
confidence: 99%